Intership Report on data merging at the bank of Portugal Internship Experience at the Bank of Portugal: A Comprehensive Dive into Full Stack Development - Leveraging Modern Technology to Innovate Financial Infrastructure and Enhance User Experience - Oliveira, Paulo Ricardo Lopes de (2023)
Internship Report presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science